REPRESENTASI MASKULINITAS DALAM FILM “BOHEMIAN RHAPSODY” (ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE) - Eva Irene, Ni Made Ayu Dwi; Sugiarica Joni, I Dewa Ayu; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2019)
ABSTRACT Film is a mass media that presents reality through certain codes and symbols in audiovisual form. There are still many messages contained in a film containing lame gender representations. One of them is the representation of masculinity. In the Bohemian Rhapsody film, Freddie Mercury is portrayed as a man who is metrosexual, likes a luxurious and elegant lifestyle, and is flamboyant. Therefore the aim of the study is to explain the representation of masculinity in the Bohemian Rhapsody film. This study uses a descriptive-qualitative approach with an interpretive constructivist paradigm with Peirce's semiotic analysis method. The result of this study indicates that the representation of masculinity reflected in this film is the masculinity of the 1980s. Freddie Mercury's masculinity of the 1980s was reflected in his metrosexual figure, lavish and elegant lifestyle, and flamboyance in the film. Keywords:Bohemian Rhapsody Film,1980 Masculinity, Representation, Semiotics Peirce